Syntax in the Written Language of Normal Hearing and Hearing Impaired Students of the 8th Standard : A Comparative Study - Laxmi Jagadish (Journal of All India Institute of Speech and Hearing, 1970)
The hearing impaired have a tough task ahead of them in terms of communication. Speech would be difficult because of their faulty perception ofthe speech sounds resulting in many defects of articulation as well as defects in the voice and resonance, which are the result of limited auditory feedback.The use of signs has often been advocated, but there limited flexibility as there are more people who do not understand signs than those who do, especially inIndia.